Working with sexual offenders: strength-based approaches and desistance factors - Pryboda, Jennifer (2015)
This thesis aims to provide a broad overview of topics relating to desistance factors and strength-based approaches to working with male sex offenders. It incorporates diverse methods, including a systematic review, an empirical study, an individual case study, and a critique of an actuarial risk assessment.